KPPU’s Institutional Challenges in Enforcing Anti-Monopoly Law against Foreign Dominated Corporations - Wiranda, Cynthia (Ilmu Hukum Prima (IHP), 2026)
Indonesia’s economic expansion during the last two decades has relied heavily on foreign investment, which has created new challenges for domestic competition law. The Komisi Pengawas Persaingan Usaha (KPPU), established under Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, serves as the guardian of fair market conduct. Despite the law’s progressive intent, its enforcement capacity has been hampered by institutional weaknesses, overlapping regulatory mandates, limited investigatory power, and insufficient judicial cooperation. These challenges are exacerbated by the rapid expansion of multinational corporations operating across Indonesia’s key sectors such as mining, telecommunications, and digital trade whose cross-border structures often outpace the jurisdictional reach of domestic regulators. Through doctrinal and qualitative analysis, this study examines the gap between the normative aspirations of Indonesia’s competition law and its practical enforcement by KPPU. The research highlights several critical issues: (1) the inadequacy of procedural mechanisms for handling transnational antitrust cases; (2) the persistent political and bureaucratic interference undermining KPPU’s institutional independence; and (3) the lack of coordination between KPPU and other economic authorities, which weakens the overall deterrent effect of competition law.The findings suggest that Indonesia’s competition regime must evolve to reflect the dynamics of globalised markets. Legal reforms should focus on enhancing KPPU’s investigative autonomy, ensuring judicial consistency in antitrust decisions, and aligning domestic enforcement with ASEAN and OECD competition standards. Strengthening KPPU’s institutional capacity and jurisdictional reach is essential not only to preserve fair competition but also to safeguard Indonesia’s economic sovereignty in the face of deepening global integration.